2005
DOI: 10.2308/jis.2005.19.2.57
|View full text |Cite
|
Sign up to set email alerts
|

The REA Pattern, Knowledge Structures, and Conceptual Modeling Performance

Abstract: Most database textbooks on conceptual modeling do not cover domainspecific patterns. The texts emphasize notation, apparently assuming that notation enables individuals to correctly model domain-specific knowledge acquired from experience. However, the domain knowledge acquired may not aid in the construction of conceptual models if it is not structured to support conceptual modeling. This study uses the Resources Events Agents (REA) pattern as an example of a domain-specific pattern that can be encoded as a k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Such experience is part of what makes them experts." [Gamma et al, (1995), p.1;Gerard, (2005), p.57]. The resilience of EZS over many centuries attests to this.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Such experience is part of what makes them experts." [Gamma et al, (1995), p.1;Gerard, (2005), p.57]. The resilience of EZS over many centuries attests to this.…”
Section: Discussionmentioning
confidence: 96%
“…Nonetheless, modern NES such as REA have proven useful as modelling tools for building databases for business (e.g., Bradford et al, 2007;Callaghan et al, 2002;Dunn et al, 2005;Gerard, 2005;Jones et al, 2002Jones et al, , 2005Jones et al, -2006Poels et al, 2007), including non-accounting databases (e.g., Vymetal et al, 2008). Consequently, there is room for both NES and EZS in a modern AIS: one as a database design tool, the other as the target of that design.…”
Section: Background For the Researchmentioning
confidence: 99%
“…Their research provides guidelines for organizations that have relatively scarce resources in a particular application domain. Gerard (2005) showed that domain-specific knowledge structures support the conceptual modeling task. Other researchers have shown that different application domains may share common knowledge structures, and that the reuse of models (capturing domain knowledge) from one domain to another is feasible and beneficial (Maiden and Sutcliffe 1992).…”
Section: Applied Domain Knowledge Quality (D3)mentioning
confidence: 99%
“…Such models can be found in requirements engineering, workflow, and business process modeling literature. Indeed, there is a large body of literature that discusses modeling techniques at a very detailed level [Dalal et al 2004, Gerard 2005, Green and Rosemann 2000, Leymann and Roller 2006, van der Aalst et al 2003, Xinming and Haikun 2006. Recognition of the distinction between business-centric and information-systems-centric conceptual models is increasing in the literature as is the awareness that knowledge of the application domain and knowledge and IS domain are not the same thing [Khatri et al,2006].…”
Section: Figure 2 Identification and Mapping During Modelingmentioning
confidence: 99%